# Marcus needs to rewrite f(x) = x^{2} + 6x + 4 in vertex form. What is the answer?

**Solution:**

Given f(x) = x^{2} + 6x + 4

This is an equation of the parabola. The vertex is at (h,k)

The vertex form of the parabola is a(x-h)^{2} +k

f(x) = x^{2} + 6x + 4 +5 -5

= x^{2} + 6x +9 -5

= ( x^{2} + 2(3)x + 32) -5

= (x+3)^{2} -5

= 1(x- (-3))^{2} -5

f(x) = 1(x- (-3))^{2} -5. This is of the vertex standard equation a(x-h)^{2} +k.

Marcus needs to rewrite f(x) = f(x) = x^{2} + 6x + 4 in vertex form. What is the answer?

**Summary: **

Marcus needs to rewrite f(x) = x^{2} + 6x + 4 in vertex form. The answer is 1(x- (-3)^{2}) -5.